A combined degradation of dyes and inactivation of viruses by UV and UV/H2O2 - Timchak, Elena; Gitis, Vitaly (Chemical engineering journal (Lausanne, Switzerland : 1996), 2012)
► Fluorescent dye degradation rate in mixtures is lower than in model solutions. ► Hydroxyl radicals are less decomposing dyes and more inactivate viruses. ► Two additional logs of MS2 inactivation were obtained in UV/0.2M H2O2. ► Phi X 174 and T4 are inactivated by direct UV irradiation only. An advanced UV/H2O2 oxidation process is a popular wastewater treatment option that combines the inactivation of pathogenic microorganisms with the oxidation of organic pollutants. While a separate decomposition of viruses and organics has been a subject of several studies, no research on the possible mutual influence of the two during UV and UV/H2O2 processes has been conducted yet. We investigated inactivation of MS2, phi X 174 and T4 viruses, alone and jointly with the degradation of two fluorescent dyes, rhodamine B and fluorescein. Complex dye-virus experiments were performed in mixed suspensions of free floating and conjugated species. The studies were performed in collimated beam and in continuous-flow UV reactors and showed that the inactivation of viruses is not affected by the presence of dyes but can be improved by the addition of hydrogen peroxide. The addition of 0.2M H2O2 at 70mJ/cm2 increased the inactivation of MS2 by two logs and had no effect on phi X 174 and T4. The bleaching of fluorescent dyes in the presence of viruses was decreased due to limited availability of hydroxyl radicals and their preferential participation in virus inactivation.